The pharmacokinetics of therapeutic proteins - Meibohm, Bernd (Henry Stewart Talks, 2019)
Differences in the pharmacokinetics of therapeutic proteins compared to small molecule drugs, Classes of therapeutic proteins, Central paradigm of clinical pharmacology, Distribution and tissue penetration of mAbs and proteins, Three methods of renal protein metabolism, Hepatic protein metabolism, Target-mediated drug disposition, Immunogenicity: general considerations and contributing factors, Neutralizing, clearing and sustaining anti-drug antibodies